Analysis of the Influence of Innovation and Celebrity Endorser towards the Business Succes of PT Bukalapak.com tbk (Case Study on STMB MULTISMART Batch 19) - Jenny; August Halomoan Siregar (Institute of Computer Science (IOCS), 2022)
The purpose of this research is to determine the effect of Innovation and Celebrity Endorser toward the Business Succes of PT Bukalapak.com tbk. This is a quantitative research. Population of this research is all of STMB MULTISMART students batch 19, with total of 95 people. The sampling technique is done by using saturation sample where all population is used as sample. This study will be distributed with questionaire which is measured by likert scale. Data analysis using multiple linier regression analysis and coefficient of determination as well as simultaneous test and partial test. The result of the research indicates that there is a positive and significant influence both partially and simultaneously where the Innovation variable partially has value of tcount (10.040) which is bigger than ttable (1.98609) with significant value (0.000) is smaller than 0.05 while Celebrity Endorser has value of tcount (2.160) bigger than ttable (1.98609) with significant value (0,035) smaller than 0.05. Simultaneously, Innovation and Celebrity Endorser variable has value of Ftable (3.06) with significant value = 5% (0.05), which are Fcount (55.345) and sig.b (0.000b). This indicates that the result of the research accepts Ha and rejects H0, while coefficient of the determination of Adjusted R Square is 0.536. This indicates that Innovation and Celebrity Endorser variable explain their influence toward PT Bukalapak.com tbk success by 53.6% while the remaining 46.4% is the influence of other independent variables that are not studied in this research. Based on this research, the implication for the company is to do more of Innovation and be more selective in choosing Celebrity Endorser.